A rare case of unicornuate uterus with non communicating rudimentary horn containing functional endometrium - Priyanka, Priyanka; Shergill, Harbhajan; Bansal, Romi; Aggarwal, Mohini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Unicornuate uterus with rudimentary horn is a rare type of anomaly. The incidence is approximately 1/100,000. Mullerian anomalies are associated with many obstetrical and gynecological complications. Non-communicating and functional rudimentary horn can cause severe pain in abdomen due to accumulation of the blood causing its distension. Authors report a case of 25 years old patient with unicornuate uterus with non-communicating rudimentary horn containing functional endometrium presenting with chief complaints of severe pain in lower abdomen associated with multiple episodes of vomiting.